Records Nos 544 and 548 in the first part of the 8th volume of The Primeval Monuments of Polish Law and their significance for the rise of the House of Konarski, coat of arms Gryf - Kruszewski, Tomasz (The Opole Studies in Administration and Law, 2020)
The author shows – on the basis of two records from old judicial books – the medieval jurisdiction against the background of the socioeconomic system of the day. As far as the regime of those times was concerned, some of the social groups came to be dependent on the Polish law and others were subjected to the laws of Western Europe. It demonstrates that in the medieval times Poland was situated between different legal cultures. Unfortunately, the laconic character of the studied records does not allow establishing the real value of the objects which the conflict concerned.